Access to Modern Energy Initiatives by Rural Household in Homa Bay County, Kenya - Donata, Odago A.; Leonard, Mulongo S.; Pacifica, Mining (Advances in Social Sciences Research Journal, 2019)
The failure to provide energy access continues in many parts of the world today. It is estimated that three million people in the world lack access to energy infrastructure and use biomass solid fuels such as charcoal firewood, dung or crop residue for cooking. Apart from being highly inefficient, these traditional, open fire cookstoves produce toxic particulates that cause indoor air pollution and contribute to around four million premature deaths per year especially among women and children. The paper based on a study undertaken in Homa Bay is focused on identifying the energy initiatives in Homa Bay County, and how consumers perceive ICS with respect to traditional stoves. The study used Ex post facto research design using mixed method to collect data which was obtained using data collection instruments such as questionnaires, FGD, Key informant interview schedules and researcher’s observation. The study used systematic and cluster sampling to get a representative data. The study was based on the capability approach theory that people ought to be made equal in their capabilities or at least in their basic capabilities. The study found that household cooking technologies came from two main source namely three stone fire and Kenya ceramic jiko. The main sources of household cooking fuel were biomass, kerosene and LPG. Use of open fire and overdependence on solid biomass resulted in respiratory illness and eye discomfort caused by IAP and black carbon. Low adoption of solar and electricity resulted in high use of kerosene tin lamp as source of light. The study concludes that there is a need to strengthen efforts to promote use of ICS, which use biomass in a more efficient way. The promotion and distribution of ICS should be linked with funding for climate-related projects, with the aim of reducing the cost of the stoves and creating added economic incentives to replace old, inefficient cookstove models.